Bucillamine as An Efficient H Atom Donor Protects High-Molar-Mass Hyaluronan from Oxidative Degradation by Effective Scavenging of Free Radicals - Valachová, Katarína; Rychlý, Jozef; Janigová, Ivica; Csomorová, Katarína; Juránek, Ivo; Šoltés, Ladislav (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
Bucillamine has been indicated to possess a protective potential towards high-molar-mass hyaluronan degradation induced by free-radical-generating system composed of cupric ions and ascorbate. In the present study, we used a multimodal approach applying a variety of methods including non-isothermal chemiluminometry, thermogravimetry and differential scanning calorimetry; with a particular focus on characterization of the hyaluronan fragments produced. Under our experimental conditions, bucillamine was found to remarkably retard oxidative degradation of high-molar-mass hyaluronan. The observed outputs, specifically the reduction in chemiluminescence intensity and disappearance of differential scanning calorimetry exotherm (at 270oC) for hyaluronan fragments, may be indicative for further studies aiming at revealing the particular mechanism(s) of action of bucillamine in this process.